2011
DOI: 10.1071/bt10175
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous Streptomyces regulate the metabolism of seedlings of Araucaria angustifolia (Coniferales) during root colonisation

Abstract: Araucaria angustifolia (Bertol.) Kuntze, known as Brazilian pine, is an endangered species of great ecological and economic importance. This species grows slowly and unevenly, with high mortality in commercial plantations. Streptomyces is a genus of soil microorganisms that may have a beneficial effect on plant growth. This study evaluated the effect of three autochthonous Streptomyces spp. isolates (PM1, PM4 and PM9) on the initial metabolism and development of A. angustifolia seedlings. The enzymatic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Consequently, the increase in the substrate for ACC oxidase elevates the endogenous concentrations of ethylene [2] and ultimately inhibits root growth. Furthermore, the contact of the rhizobacteria with the developing roots can cause a delay in the initial plant growth due to the deviation in the cellular metabolism to recognize and establish the rhizobacteria-plant interaction, a trade-off often reported in this type of interaction [11,14,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the increase in the substrate for ACC oxidase elevates the endogenous concentrations of ethylene [2] and ultimately inhibits root growth. Furthermore, the contact of the rhizobacteria with the developing roots can cause a delay in the initial plant growth due to the deviation in the cellular metabolism to recognize and establish the rhizobacteria-plant interaction, a trade-off often reported in this type of interaction [11,14,45].…”
Section: Discussionmentioning
confidence: 99%
“…Rouws [4,10]. Strains of Streptomyces species originating from an Araucaria forest were characterized as PGPR, based on their capacity for IAA production [11], phosphate solubilization, antibiosis, and production of siderophores [12]. Some studies have shown a positive effect of Streptomyces spp.…”
Section: Introductionmentioning
confidence: 99%
“…As such, Streptomyces strains may enhance the supply of plant nutrients, produce IAA, cytokinins, and siderophores, increase the solubility of phosphate, and control plant pathogens through antibiosis and the production of phenazines. [14][15][16][17][18][19] Horstmann et al 20 isolated Streptomyces sp. from the Fabaceae rhizosphere and tested its plant growth-promoting properties, including siderophore production, 1-aminocyclopropane-1-carboxylate (ACC) deaminase, IAA, and phenazines.…”
Section: Introductionmentioning
confidence: 99%